Funder and facilitator: Swedish development aid aimed at cultural heritage in Bosnia and Herzegovina 1995–2008. Issue 7 (10th November 2019) - Stengård, Malin; Legnér, Mattias
ABSTRACT: The paper investigates the relationship between the Swedish development agency Sida and Cultural Heritage without Borders (CHwB), a facilitating organisation in the field of cultural heritage in Bosnia and Herzegovina (BiH) following the Bosnia War. From 1995 to 2008 CHwB was the only NGO in BiH working to preserve cultural heritage, and was almost exclusively funded by Sida. From having been an organisation focusing on the restoration of historic monuments, CHwB transformed into becoming an NGO facilitating social and economic development. The paper suggests that CHwB gradually changed from having a very particular position of working with the preservation of an ethnically diverse cultural heritage with the aim of promoting reconciliation, to one where it needed to focus on reconstruction and its implications for economic development. By analysing a large number of key documents using Norman Fairclough's critical discourse analysis this change is interpreted in relation to changes taking place within the landscape of international aid and post-conflict recovery.